Three stones make a wall the story of archaeology - Cline, Eric H. (Princeton Princeton University Press, 2017)
"In 1922, Howard Carter peered into Tutankhamun's tomb for the first time, the only light coming from the candle in his outstretched hand. Urged to tell what he was seeing through the small opening he had cut in the door to the tomb, the Egyptologist famously replied, 'I see wonderful things.' Carter's fabulous discovery is just one of the many spellbinding stories told in Three Stones Make a Wall. Written by Eric Cline, an archaeologist with more than thirty seasons of excavation experience, Three Stones Make a Wall traces the history of archaeology from an amateur pursuit to the cutting-edge science it is today by taking the reader on a tour of major archaeological sites and discoveries, from Pompeii to Petra, Troy to the Terracotta Warriors, and Mycenae to Megiddo and Masada. Cline brings to life the personalities behind these digs, including Heinrich Schliemann, the former businessman who excavated Troy, and Mary Leakey, whose discoveries advanced our understanding of human origins. The discovery of the peoples and civilizations of the past is presented in vivid detail, from the Hittites and Minoans to the Inca, Aztec, and Moche. Along the way, the book addresses the questions archaeologists are asked most often: How do you know where to dig? How are excavations actually done? How do you know how old something is? Who gets to keep what is found? Taking readers from the pioneering digs of the eighteenth century to the exciting new discoveries being made today, Three Stones Make a Wall is a lively and essential introduction to the story of archaeology"-- |c Provided by publisher.
Preface: A Petrified Monkey's Paw -- Prologue: "Wonderful Things" : King Tut and His Tomb -- Section I. Early Archaeology and Archaeologists -- Ashes to Ashes in Ancient Italy -- Digging Up Troy -- From Egypt to Eternity -- Mysteries in Mesopotamia -- Exploring the Jungles of Central America -- Digging Deeper #1: How Do You Know Where To Dig? -- Section II. Africa, Europe, and the Levant : Early Hominins to Farmers -- Discovering Our Earliest Ancestors -- First Farmers in the Fertile Crescent -- Section III. Excavating the Bronze Age Aegean -- Revealing the First Greeks -- Finding Atlantis? -- Enchantment Under the Sea -- Section IV. Uncovering the Classics -- From Discus-Throwing to Democracy -- What Have the Romans Ever Done for Us? -- Digging Deeper #2: How Do You Know How To Dig? -- Section V. Discoveries in the Holy Land and Beyond -- Digging Up Armageddon -- Unearthing the Bible -- Mystery at Masada -- Cities of the Desert -- Digging Deeper #3: How Old is This and Why is it Preserved? -- Section VI. New World Archaeology -- Lines in the Sand, Cities in the Sky -- Giant Heads, Feathered Serpents, and Golden Eagles -- Submarines and Settlers; Gold Coins and Lead Bullets -- Back to the Future -- Epilogue: Do You Get to Keep What You Find?
Includes bibliographical references (pages 383-429) and index.
Keywords: Archaeology -- History; Excavations (Archaeology) -- History; Archaeologists -- Biography; Archaeology -- Methodology; Antiquities; Civilization, Ancient